Spoken Communication with CAMBADA@Home Service Robot - Martins, Ciro
Spoken language is a natural way to control the human-robot interac-tion, especially for mobile service robots. It has some important advantages over other communication approaches: eyes and handsfree, communication from a distance, even without being in line of sight and no need for additional learning for humans. In this paper, we present the spoken dialog framework in-tegrated in our mobile service robot CAMBADA@Home, a robotic platform aimed at move into a living space and interact withusers of that space. The proposed framework comprises three major spoken andnatural language processing components: an Automatic Speech Recognition component to process the human requests, a Text-to-Speech component to generate more nat-ural responses from the robot side, and a dialog manager to control how these two components work together.